Bimbingan Penyuluhan Terhadap Bahaya Virus Covid-19 Dengan Perilaku Hidup Bersih dan Sehat (PHBS) - Noffiyanti, Noffiyanti; Mauliddia, Priska Amanda (Konseling Edukasi : Journal of Guidance and Counseling, 2021)
Counseling Guidance on the Danger of the Covid-19 Virus with Clean and Healthy Living Behavior. This study aims to investigate the Covid-19 Covid-19 Counseling Guidance with Clean and Healthy Living Behavior (PHBS). In this study using a descriptive qualitative approach. This approach was chosen because it wanted to explore the existing picture in the field related to the implementation of Covid-19 Covid-19 Counseling with Clean and Healthy Behavior (PHBS) in the family and society at large. The technique of collecting data uses participatory observation, in which the researcher is directly involved with the community in order to find out the habits of the community. The data obtained from the observations will later be collected and analyzed using structural analysis. The results showed that the emergence of the Covid-19 outbreak encouraged the importance of providing education to the public about Clean and Healthy Living Behaviors (PHBS). In addition, the public needs to know for sure the transmission of the Covid-19 Virus and Covid-19 Prevention Methods, namely by staying at home, and must use a mask when leaving the house and try not to have physical contact with other people. Always wash your hands and apply PHBS. PHBS is the right strategy to prevent the spread of Covid-19. The public continues to be urged to always improve a Clean and Healthy Lifestyle in an effort to prevent the spread of Covid-19. Because people's behavior plays an important role in reducing the spread of the Covid-19 Pandemic which is very effective and easy for all levels of society to do. Government recommendations continue to call on the PHBS movement to be the key to preventing the spread of the epidemic that has spread widely throughout the world. Conducting a Clean and Healthy Life Behavior is expected to prevent the spread of Covid-19 so that incidents do not increase. Therefore it is very important to carry out a Clean and Healthy Lifestyle, it needs to be applied continuously so that it can increase the knowledge of all levels of society to apply PHBS in everyday life.Keywords: Society, Covid-19, Clean and Healthy Lifestyle